Association of infectious disease history with wasting among Indonesian toddler in coastal areas - Kapantow, Nova Hellen; Kairupan, Ralph; Sanggelorang, Yulianty (International Journal Of Community Medicine And Public Health, 2022)
Background: Wasting prevalence in Indonesian toddler has been decreasing from 2013 to 2018 (12.12-10.19%), but this number remains in medium category according to WHO. Identification of risk factors by looking at infectious disease history as the cause of wasting can provide information to appropriate intervention. This research aimed to analyze the association between infectious disease history with wasting in toddler. Methods: This research was an observational analytic study with cross sectional approach, which was carried out for 6 months, from April to October 2021. The sample population was children aged 36-59 months, who lived with their mothers in the coastal areas of the Siau Tagulandang Biaro Regency, North Sulawesi Province. Sampling was done by purposive sampling to get 221 samples. Data collection using questionnaires by interview, secondary data in the maternal and child health (MCH) book, and anthropometric measurements namely body mass index by age, for wasting variables. Results: The results showed the history of infectious disease (p value =0.045; OR=3.491) and mother’s education (p value =0.025) have significant relationship with wasting among Indonesian toddler. The results of the analysis on history of exclusive breast feeding, birthweight, immunization status and father’s education, showed no significant relationship with wasting (p>0.05). Conclusions: Wasting among toddler can be prevent by controlling many factors, such as keeping them safe from infectious diseases, also ensure that every mother and mother-to-be gets a proper education.